Modulation of Cyp450, ALS1 and COX-2 signaling pathways induced by Candida albicans infection via novel antifungal agents - Rehab M Abdel Megeed; Dalia B. Fayed; Amira Abood; Mai O Kadry (Elsevier, 2018)
Although, fluconazole is widely used in clinical treatment as an antifungal drug, it recorded potential problems as resistance and intracellular accumulation. Female albino mice were injected with single ip dose of Candida albicans (1.5 × 106 CFU). Three weeks post treatment with fluconazole and two novel synthesized compounds [(2-(4-(Pyridin-2-yl) aminosulfonylphenylamino)-6-(naphthalen-2-yl)-4-(pyridin-2-yl) pyridine-3carbonitrile) and (2-(4-(Pyrimidin-2-yl) aminosulfonylphenylamino)-6-(naphthalen-2-yl)-4-(pyridine-2-yl)pyridine-3-carbonitrile) (13b & 14b, respectively)] in both low and high doses (50 mg/kg & 200 mg/kg), liver function and vaginal inflammation were assessed. Candida albicans significantly elevated serum alanine aminotransferase (ALT) and butrylcholinesterase (BCHE) as well as hepatic malondialdehyde (MDA). Molecular analysis confirmed a significant up-regulation in mRNA gene expression of Agglutinin-like sequence (ALS1), hepatic cytochrome p450 (Cyp450). Vaginal COX-2 gene expression was also elevated. Nevertheless, a significant down-regulation was apparent in mice treated with the aforementioned compounds. Meanwhile, administration of 14b in a high dose noticeably down-regulated the altered parameters expression showing a significant effect in comparison to animals treated with the variable doses of the tested compounds. Histopathological finding confirmed the obtained results. The current work investigated the efficiency of new synthetic pyrimidine derivatives 14bas anti-microbial agents and recommended to be improved and evaluated as a novel antifungal drug to overcome the emergence of resistance problem.